Basic Myanmar: Myanmar level 1 - Than, Daw Thi Da (Universiti Putra Malaysia Press, 2001)
Years of experience teaching the Burmese language at the Universiti Putra Malaysia has led Daw Thi Da Than to produce this course book. It is structured to allow the student to learn Burmese word sounds, orthography, vocabulary, and everyday expressions in a fuss-free, straightforward way.